Environmental and cost impacts of maximizing renewable energy resources for the Visayas electric power grid - Isidro, Charito Martinez (2006., 2006)
This study aims to determine the environmental and cost impacts of developing renewable energy resources in the Visayas to meet the future requirements of the Visayas Electric Power Grid. Power system planning models and processes were employed (1) to see whether renewable energy resources in the Visayas could support long term in the Visayas; (2) to determine the cost of implications of maximizing the utilization of renewable energy resources in the Visayas Electric Power Grid; and (3) to determine the amount of air emissions that would result from a maximized renewable energy scenario.
It was found out that it was possible to delay the construction of coal -fired power plants in the Visayas on the condition that renewable energy development will be pursued in an aggressive manner. Geothermal, hydro, biomass and wind resources in the Visayas could serve as base load plants and be able to displace the need for coal-fired power plants. An aggressive approach to renewable energy development could displace coal-fired generation technologies in the Visayas that by the year 2024, no more coal plants are needed in the Visayas Grid.
It was also foud out that such development would result in average electric generation costs that are lower than a business-as-usual scenario, dismissing notions that the pursuit for clean energy development would be expensive.
"May 2006."
Thesis (M.S. Energy Engineering)-University of the Philippines Diliman.
Keywords: Renewable energy sources -- Philippines (Visayas).; Energy sources, renewable; Power resources -- Philippines(Visayas).